2014
DOI: 10.1002/pat.3386
|View full text |Cite
|
Sign up to set email alerts
|

Conductive elastomeric nanocomposites based on oxidation of aniline with silver nitrate via inverse emulsion polymerization

Abstract: The present investigation describes a facile and rapid approach of conductive nanocomposites production and assesses the opportunity of their use as electro-mechanical sensors. Hybrid materials containing silver and polyaniline nanoparticles reinforcing a thermoplastic elastomeric matrix were studied. The approach developed includes ultrasonically assisted in situ inverse emulsion polymerization of aniline oxidized by a weak oxidant and silver nitrate, and supported with a strong oxidant, ammonia peroxydisulfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…(a)), with a corresponding increase of stress at break (Fig. (b)), in agreement with literature data . The mechanical properties for the SIS‐22% nanocomposites are significantly higher than for the SIS‐14% because of higher polystyrene content.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…(a)), with a corresponding increase of stress at break (Fig. (b)), in agreement with literature data . The mechanical properties for the SIS‐22% nanocomposites are significantly higher than for the SIS‐14% because of higher polystyrene content.…”
Section: Resultssupporting
confidence: 90%
“…This concept is based on positioning conductive features at the interface of the polymer particles instead of random distribution in the polymer matrix . The methodology developed preserves and controls the dispersion morphology of nanoelements in the main matrix . The approach developed consists of two main steps: precipitation and filtration processes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 3320 cm ‐1 indicates N‐H stretching, the spectra of homopolymers or copolymer have two major absorption bands at 1583 cm ‐1 and 1511 cm ‐1 . These bands can be attributed to the C = C vibrations of quinoid and benzenoid units respectively …”
Section: Resultsmentioning
confidence: 99%
“…These bands can be attributed to the C = C vibrations of quinoid and benzenoid units respectively. [20][21][22] The number of quinoid units was almost lower than the number of benzoid units in either homopolymers (PANI and PAA) or copolymer (PANAA) as there was an apparent difference in the relative intensity of quinoid to benzoid band. This reveals to the degree of the oxidation in the polymer chains.…”
Section: Ft-ir Spectral Studiesmentioning
confidence: 99%
“…So, the incorporation of metal NPs can effectively enhance the electrical, optical and other properties of polymers and their composites. [13,14] PANi-Ag and PANi-Au composite nanofibers prepared by Pillalamarri et al were reported to have higher electrical conductivity as compared with neat PANi, and this reveals the significance of noble metal NPs in improving the conductivity of PANi. The increase in the electrical conductivity of PANi because of the addition of NPs can enhance the microwave absorption properties via the enhancement in the dielectric losses.…”
Section: Introductionmentioning
confidence: 90%